2014
DOI: 10.1176/appi.focus.12.1.90
|View full text |Cite
|
Sign up to set email alerts
|

CBT for Insomnia in Patients with High and Low Depressive Symptom Severity: Adherence and Clinical Outcomes

Abstract: Study Objectives: To evaluate whether depressive symptom severity leads to poorer response and perceived adherence to cognitive behavioral therapy for insomnia (CBTI) and to examine the impact of CBTI on well-being, depressive symptom severity, and suicidal ideation. Design: Pre-to posttreatment case replication series comparing low depression (LowDep) and high depression (HiDep) groups (based on a cutoff of 14 on the Beck Depression Inventory [BDI]). Participants: 127 men and 174 women referred for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 24 publications
5
62
1
Order By: Relevance
“…This finding supports past work indicating that rumination and worry are discrete constructs, 27 that rumination differentiates good and poor sleepers, 26 and that it contributes to sleep quality 47 ; but, it is also consistent with Manber and colleagues' 22 suggestion that the efficacy of CBTI may be enhanced among individuals with comorbid insomnia and depression by paying greater attention to cognitive factors. Specifically, intervention for insomnia symptoms in the context of meaningful depression may be improved by targeting rumination related to daytime symptoms of insomnia.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding supports past work indicating that rumination and worry are discrete constructs, 27 that rumination differentiates good and poor sleepers, 26 and that it contributes to sleep quality 47 ; but, it is also consistent with Manber and colleagues' 22 suggestion that the efficacy of CBTI may be enhanced among individuals with comorbid insomnia and depression by paying greater attention to cognitive factors. Specifically, intervention for insomnia symptoms in the context of meaningful depression may be improved by targeting rumination related to daytime symptoms of insomnia.…”
Section: Discussionsupporting
confidence: 89%
“…Although a recent trial showed that group cognitive behavioral therapy for insomnia (CBTI) worked equally well at reducing insomnia among those treatment completers with high and low depression severity, insomnia severity remained higher among those with greater depression severity throughout treatment. 22 Thus, questions remain as to how to enhance interventions to more effectively reduce insomnia severity in patients with depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CBT-I has been shown to reduce depressive symptom severity and to have other benefi ts, such as better perceived energy levels, productivity, and self-esteem. 3,4 Several studies identifi ed predictors of improvements in insomnia following CBT-I. 5,6 However, to the best of our knowledge, factors associated with the effects of CBT-I on depressive symptom severity have not been examined.…”
mentioning
confidence: 99%
“…Improvements in sleep quality have been shown to significantly reduce anxiety, depression, and suicidal ideation [25][26][27][28]. In 2013, the US Veterans Affairs Department of Defense included sleep disturbances in their practice guidelines for those at risk of suicide [29].…”
Section: Men In Midlifementioning
confidence: 99%